Tracheoesophageal Voice Prosthesis Use and Maintenance in Laryngectomees - Brook, Itzhak; Goodman, Joseph F (International Archives of Otorhinolaryngology, 2020)
Tracheoesophageal speech is the most common voicing method used by laryngectomees. This method requires the installation of tracheoesophageal prosthesis (TEP), which requires continuous maintenance to achieve optimal speaking abilities and prevent fluid leakage from the esophagus to the trachea. The present manuscript describes the available types of TEPs, the procedures used to maintain them, the causes for their failure due to fluid leakage, and the methods used for their prevention. Knowledge and understanding of these issues can assist the otolaryngologist in caring for laryngectomees who use tracheoesophageal speech.
Keywords: tracheoesophageal voice prosthesis; tracheoesophageal prosthesis maintenance; laryngectomees; sputum; speech outcomes